Artificial Intelligence-Assisted Writing Application for Improving Writing Skills of Islamic Education Students - Fauziah, Zumrotul; Minarti, Sri (Jurnal Kependidikan Islam, 2023)
This study is aimed to illuminate the use of AI-assisted writing applications to improve academic writing skills and describe how to implement AI-assisted writing applications for EFL academic writing. This study is qualitative reasearch. The data is collected through analysis of writing task and interview about the use of Artificial Intelligence in academic writing. After analyzing students’ writing task and interview related to the use of AI in language teaching, especially in writing. The study revealed that the use of AI-assisted applications is beneficial for students, especially students of Islamic education study program. The applications could help the students construct paragraphs, correct the structures, and even paraphrase the paragraphs. The use of AI in writing will not replace human existence since AI-assisted writing application is just a tool, there should be creativity and logical reasoning in writing an academic article. The use of Artificial intelligent-assisted applications could be applied as new model to increase students’ writing skills since there are many features and easiness offered by AI technology.